A trajetória histórica da segurança alimentar e nutricional na agenda política nacional: Projetos, descontinuidades e consolidaç\~ao - Sandro Pereira Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– The trajectory of the food and nutritional security in the government agenda was marked throughout the twentieth century by a series of discontinuities, low degree of centrality in the general political and few social results. This work aims to analyze this historical trajectory and evaluate the different raids the theme of food security in the government agenda. Since 2003 this topic has gained a new operational approach, the main element of the strategy of Zero Hunger Program. When checking the operation of actions triggered from the launch of this program, this paper divided for analytical purposes into six action lines, it was noted that they were getting stronger over the years. The conclusion is that the engineering proposal and established to the Zero Hunger Program provided the main framework for the institutionalization of food and nutritional security in the public policy agenda. But we cannot forget that it was a strategy totally context dependent, and only managed to secure this institutionalization of a series of measures and actions earlier.
Keywords: I38; 330; food security and nutrition; eradication of hunger; government agenda; public policy; Zero Hunger Program